Comprehensive Assessment of the Relationship Between MicroRNA-124 and the Prognostic Significance of Cancer - Sun, Yadong; Duan, Fujiao; Liu, Weigang; Peng, Zhen; Dai, Liping; Feng, Yajing; Yang, Zhenxing; Shang, Jia; Wang, Kaijuan (Frontiers in Oncology, 2018)
Background: Numerous studies have demonstrated the presence of microRNA-124 abnormalities involving gene expression, methylation, and single nucleotide polymorphism (SNP) in multiple and diverse cancers，but the prognostic value of these abnormalities in cancer remains inconclusive. Objective: The aim of this study is to determine the prognostic value of miR-124 in cancer. Methods: We scrutinized the electronic databases and estimate the association between miR-124 expression, methylation and SNPs and prognosis in cancers. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) for overall survival (OS), and disease-free survival (DFS)/recurrence-free survival (RFS)/progression-free survival (PFS) were calculated to estimate the effects of miR-124 expression, methylation and SNPs on cancer prognosis. The Quality In Prognosis Studies (QUIPS) and Newcastle-Ottawa Scale (NOS) were utilized to assess the quality of included studies. Results: A total of 20 studies involving 3574 participants were analyzed in evidence synthesis. Our findings showed that the low expression of miR-124 was significantly associated with poor OS (HR=2.37, 95%CI: 1.91–2.94, P=0.00; HR=3.10, 95%CI: 2.04–4.70, P=0.00) and PFS/RFS (HR=2.21, 95%CI: 1.50–3.26, P=0.00; HR=2.12, 95%CI: 1.20–3.74, P=0.00). The hyper-methylation of miR-124 was associated with poor OS (HR=2.09, 95% CI: 1.48–2.95, □□=0.00) and PFS (HR=3.70, 95% CI: 1.72–7.97, □□=0.00) (Table 3). The patients carrying with Allele C of miR-124 rs5315649 had a worse OS (HR=1.50, 95% CI: 1.09–2.07, □□=0.00) and PFS (HR=1.67, 95% CI: 1.20–2.33, □□=0.00) than the carriers with Allele G. Conclusion: The low expression and hyper-methylation of miR-124 was strongly associated with poor prognosis, and genetic variations of miR-124 rs531564 affected prognosis in cancer patients.